Evaluation of BioPlex 2200 tTG-IgA Diagnostic Performance for Serology-Based Diagnosis of Celiac Disease. Issue 1 (20th September 2021) - Pacheco, M Cristina; Lee, Dale; Dickerson, Jane
Abstract: Objectives: Forgoing biopsy for the diagnosis of celiac disease in children with tissue transglutaminase immunoglobulin A (tTG-IgA) levels greater than or equal to 10 times the upper limit of normal (≥10×ULN) has been advocated by the European Society of Paediatric Gastroenterology, Hepatology and Nutrition. Methods: Our retrospective study tested the specificity and positive predictive value (PPV) of the BioPlex 2200 assay (Bio-Rad Laboratories) in diagnosing celiac disease at the ≥10×ULN tTG-IgA threshold, which is ≥150 U/mL (negative <15 U/mL). We used the tTG-IgA and duodenal biopsy results within 6 months following tTG-IgA measurements from 542 patients who had any number of duodenal biopsy fragments, of whom 165 patients had 5 or more tissue fragments. Sensitivity and specificity of the test were calculated using histology as the gold standard for Marsh class 2 and above. Results: For histopathologic findings in the duodenum with Marsh 2 and higher, the specificity and PPV of the BioPlex 2200 at ≥10×ULN tTG-IgA were 99.5% and 95.4% using all biopsies and 97.9% and 94.9% for biopsies with 5 or more tissue fragments. Conclusions: Should clinical considerations preclude endoscopy, the BioPlex 2200 assay at ≥10×ULN TTG-IgA could be considered highly suggestive of disease.